Novel use of activated carbon fabric to mitigate smoke taint in grapes and wine. (27th February 2022) - Wilkinson, K.L.; Ristic, R.; Szeto, C.; Capone, D.L.; Yu, L.; Losic, D.
Abstract: Background and Aims: Grapegrowers and winemakers, around the world, are searching for strategies to mitigate the compositional and sensory consequences of grapevine exposure to smoke from wildfires. This study evaluated the use of activated carbon fabrics as protective coverings to mitigate the uptake of smoke‐derived volatile phenols by grapes, and accordingly, the intensity of smoky, ashy characters in wine. Methods and Results: Smoke was applied to Mataro grapes, with and without individual bunches being enclosed in bags made from three activated carbon fabrics (felt, light cloth and heavy cloth). Wine made from smoke‐exposed grapes had an elevated concentration of volatile phenols, but the composition of wines made from grapes protected by activated carbon fabric was comparable to that of the Control wine; the difference in concentration of guaiacol, o ‐ and m ‐cresol and/or syringol was only 1 μg/L. Wine made from smoke‐exposed grapes had diminished fruit and prominent smoke characters, whereas the sensory profile of the wines corresponding to activated carbon fabric treatments could not be differentiated from that of the Control wine. Analysis by GC/MS of the activated carbon fabrics following repeated smoke exposure confirmed their adsorption of smoke volatiles. Conclusions: The activated carbon fabrics successfully protected Mataro grapes and wine from being tainted by smoke exposure. Significance of the Study: This study demonstrates a promising new technology for overcoming smoke taint, an issue of major concern for grape and wine producers worldwide.